The instructional development process of a multimedia courseware on UNIMAS online learning system - Chieng, King Seng (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project focuses on the instructional development process of a computerbased multimedia learning environment. This learning environment is proposed to enhance users’ skill in using the current online learning system, Morpheus system, in Universiti Malaysia Sarawak (UNIMAS). The instructional developement process of the learning environment was based on the reflective, recursive design and development (R2D2) model. This project describes the design and development processes of the various components of the learning environment into the single-path prototype, and later to the alpha, and beta versions, based on the three guiding principles: (a)recursive, nonlinear design; (b)reflective design; and (c) participatory design. The development of this learning environment provides evidence on the feasibility of employing a constructivist instructional model to guide the instructional development process of computerbased multimedia learning environment.